Psychrophilic enzymes: structural adaptation, pharmaceutical and industrial applications - Parvizpour, Sepideh; Hussin, Nurulfarhana; Shamsir, Mohd Shahir; Razmara, Jafar (Springer, 2020)
Psychrophiles are cold-living microorganisms synthesizing enzymes that are permanently active at almost near-zero temperatures. Psychrozymes are supposed to be structurally more flexible than their homologous proteins. This structural flexibility enables these proteins to undergo conformational changes during catalysis and improve catalytic efficiency at low temperatures. The outstanding characteristics of the psychrophilic enzymes have attracted the attention of the scientific community to utilize them in a wide variety of industrial and pharmaceutical applications. In this review, we first highlight the current knowledge of the cold-adaptation mechanisms of the psychrophiles. In the sequel, we describe the potential applications of the enzymes in different biotechnological processes specifically, in the production of industrial and pharmaceutical products.